PAH distributions in sediments in the oil sands monitoring area and western Lake Athabasca: Concentration, composition and diagnostic ratios. (June 2016) - Evans, Marlene; Davies, Martin; Janzen, Kim; Muir, Derek; Hazewinkel, Rod; Kirk, Jane; de Boer, Dirk
Abstract: Oil sands activities north of Fort McMurray, Alberta, have intensified in recent years with a concomitant debate as to their environmental impacts. The Regional Aquatics Monitoring Program and its successor, the Joint Canada-Alberta Implementation Plan for Oil Sands Monitoring (JOSM), are the primary aquatic programs monitoring this industry. Here we examine sediment data (collected by Ekman grabs) to investigate trends and sources of polycyclic aromatic hydrocarbons (PAHs), supplementing these data with sediment core studies. Total PAH (ΣPAH) concentrations were highest at Shipyard Lake (6038 ± 2679 ng/g) in the development center and lower at Isadore's Lake (1660 ± 777 ng/g) to the north; both lakes are in the Athabasca River Valley and lie below the developments. ΣPAH concentrations were lower (622–930 ng/g) in upland lakes (Kearl, McClelland) located further away from the developments. ΣPAH concentrations increased at Shipyard Lake (2001–2014) and the Ells River mouth (1998–2014) but decreased in nearshore areas at Kearl Lake (2001–2014) and a Muskeg River (2000–2014) site. Over the longer term, ΣPAH concentrations increased in Kearl (1934–2012) and Sharkbite (1928–2010) Lakes. Further (200 km) downstream in the Athabasca River delta, ΣPAH concentrations (1029 ± 671 ng/g) increased (1999–2014) when %sands were included in the regression model; however, 50 km to the east, concentrations declined (1926–2009) in Lake Athabasca. Ten diagnostic ratios based on anthracene, phenanthrene, fluoranthene, pyrene, benz[ a ]anthracene, chrysene, indeno[123- cd ]pyrene, dibenz[ a, h ]anthracene, dibenzothiophene and retene were examined to infer spatial and temporal trends in PAH sources (e.g., combustion versus petrogenic) and weathering. There was some evidence of increasing contributions of unprocessed oil sands and bitumen dust to Shipyard, Sharkbite, and Isadore's Lakes and increased combustion sources in the Athabasca River delta. Some CCME interim sediment quality guidelines were exceeded, primarily in Shipyard Lake and near presumed natural bitumen sources. Graphical abstract: Highlights: We synthesized PAH sediment distributions in the oil sands area over 1997–2014. Highest concentrations were in the development center and near bitumen outcrops. There was some evidence of increasing PAH concentrations in the Athabasca delta. Diagnostic ratios provide some insight into PAH sources and trends. PAH concentrations generally were below CCME guidelines. Abstract : While PAH distributions have changed with the expanding oil sands industry, sediment mobility and a variety of natural and industry influences mute specific identification.